EL ROL DE LA FAMILIA EN LOS PROBLEMAS CONDUCTUALES DE LOS USUARIOS DEL CENTRO DIURNO DE DESARROLLO INTEGRAL PARA PERSONAS CON DISCAPACIDAD MIES – LOJA Y LA INTERVENCIÓN DEL TRABAJO SOCIAL - Quezada Castillo, Liz Alexandra (2020)
The present research is framed in the current reality of the role that the family plays in the behavioral problems of people with disabilities, being this a group of priority attention which requires the necessary attention to be able to develop on the basis of autonomy and social inclusion promoting the active participation of the family and society. The objectives set out in the research are aimed at determining the role played by the family in the behavioural problems of the Day Centre users, as well as identifying the behavioural problems presented by the users and finally the elaboration of a proposal for social intervention that will allow the strengthening of family co-responsibility. The methodological process used to achieve the objectives was based mainly on methods such as; scientific, inductive, deductive, analytical and synthetic, which contributed to the collection of data and information relevant to the development of the research. Likewise, techniques such as direct observation, interviews and surveys were used, all of which were applied from a Social Work perspective. The main findings obtained in the research show that the family plays several roles, which have an impact on the different behavioral problems presented by the users, where they as parents and/or representatives must assume and accept first that their family member has a disability, which will allow them to lead a normal life, The role of solidarity refers to the support that the family must provide to the user based on love, care and protection. As regards the role of the educator, this is about the education that the family must provide to persons with disabilities, which must not be centered on differential treatment or overprotection. 5 The results of the research process led to conclusions and recommendations for family members and/or representatives of users and professionals working at the Day Centre for the Comprehensive Development of Persons with Disabilities, with the aim of strengthening family co-responsibility. Taking into consideration the conclusions and recommendations, a proposal for social intervention was designed with the aim of strengthening family co-responsibility in order to improve family relations.